Commercialization of cholbe Robi Application & Robi’s Association with A2I at Robi Axiata Limited - Meherin, Anika (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.